2012
DOI: 10.1111/j.1365-2915.2012.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotominae of epidemiological importance in cutaneous leishmaniasis in northwestern Argentina: risk maps and ecological niche models

Abstract: In Argentina, 58.2% out of the 8126 Cutaneous Leishmaniasis (CL) incident cases accumulated from 1954 to 2006 were reported in the provinces of Salta and Jujuy. The aim of this study was to develop an exploratory risk map and a potential distribution map of the vector, in order to offer recommendations for CL prevention. A total of 12 079 Phlebotominae (Diptera: Psychodidae) belonging to the species Lutzomyia neivai (Pinto), Lu. migonei (França), Lu. cortelezzii (Brèthes), Lu. shannoni (Dyar), Lu. quinquefer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 32 publications
3
37
0
8
Order By: Relevance
“…The influence of temperature has been considered not only on the biology and ecology of sand flies (rate of egg production, development of the juvenile stages, number of annual generations, feeding activity, period of activity and survival of adults), but also on the development of the parasite inside the vector (Rioux et al, 1969;Elnaiem et al, 1998;Ready, 2008;Martín Sánchez et al, 2009;Hartemink et al, 2011). Rainfall has been associated with the activity period of sand flies, particularly in some South American foci (Queiroz et al, 2012;Quintana et al, 2012). In the present study, both species were found in a similar range of climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of temperature has been considered not only on the biology and ecology of sand flies (rate of egg production, development of the juvenile stages, number of annual generations, feeding activity, period of activity and survival of adults), but also on the development of the parasite inside the vector (Rioux et al, 1969;Elnaiem et al, 1998;Ready, 2008;Martín Sánchez et al, 2009;Hartemink et al, 2011). Rainfall has been associated with the activity period of sand flies, particularly in some South American foci (Queiroz et al, 2012;Quintana et al, 2012). In the present study, both species were found in a similar range of climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[16] because of the earlier paucity of verified presence records for L. intermedia and L. neivai . A published niche model of L. neivai is restricted to north-west Argentina because it is based on field-collected data [18]. However, datasets and methods are frequently being improved [19, 23–25], and the present report is the first to investigate how differences in the fundamental ecological niches of L. intermedia and L. neivai could affect their future distributions throughout South America.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, they reported high abundance of L. longipalpis in the rainy season, and in L. cruzi followed moderate to regular precipitation and minimum temperature elevation. Quintana et al [29] showed that precipitation seasonality and precipitation in the warmest quarter were the variables that most contributed to the ENM of Lutzomyia neivai and Lutzomyia migonei in Argentina. Our results suggest that precipitation of driest quarter and precipitation of driest month were the most important variables in L. migonei model prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, we included the sandflies species within small records sizes, in order to evaluate the accuracy of obtained models in such taxa. We compiled a country database (from 21 (29). Lutzomyia pseudolongipalpis was not included in this study because its known distribution is only restricted to three close localities in Lara state.…”
Section: Species Recordsmentioning
confidence: 99%
See 1 more Smart Citation